PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP LANSIA DALAM MENERAPKAN PROTOKOL KESEHATAN COVID-19 - Arvida. Bar; Febriyati Nengsih; Dewi Masyitah; Sovia Sovia (NHM PRESS, 2021)
Covid-19 is a new type of virus that can infect the human respiratory tract, causing mild to severe symptoms such as MERS and SARS. The elderly are one of the sub-populations in the community that are vulnerable to being infected with COVID-19. The prevalence of the incidence of COVID-19 in the world at the age of 60 years is 17.4%. The purpose of this study was to obtain an overview of the knowledge and attitudes of the elderly in efforts to prevent Covid-19. The method used is a pre-experiment using an intact group comparison research design. The variables of this study are the independent variable of health education and the dependent variable is the knowledge and attitudes of the elderly about the COVID-19 health protocol. Data were collected using questionnaire sheets through leaflets and videos before and after giving health education. The population of the study was the elderly ISPA, totaling 100 people in the Kasang Pudak Public Health Center area with a total sample of 100 respondents. Calculation of the sample using the Wilcoxon formula. How to analyze it using the Wilcoxon test with a significant level of P <0.05. The provision of health education using leaflet and video media affects the knowledge and attitudes of the elderly in the hope that the elderly can take a good attitude in implementing the COVID-19 health protocol.